ASSESMENT OF THE WATER QUALITY IN SIRET HYDROGRAPHIC BASIN - VIOLETA NĂSTUNEAC; SIMONA GAVRILAȘ; FLORENTINA-DANIELA MUNTEANU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The current study is focusing on the evaluation of the quality of surface water from the Siret hydrographic basin. For this purpose, was used the Global Pollution Index (I*GP), which was calculated for eleven water sampling points from Siret Basin. The sampling was performed for a period between the years 2010 and 2014. In the study were considered the following physicochemical parameters: pH, dissolved oxygen, chemical and biochemical oxygen demand, nitrogen compounds, phosphorus, iron, manganese, cadmium, mercury, nickel, lead, copper, zinc, and chromium. A specific quality index was calculated by considering the provisions of the law and an evaluation score was determined for each of the monitored water parameters. Finally, the global pollution indexes were determined, and based on these values could be evaluated the water pollution state. The results show that the situations when the pollution is creating discomfort effects on the environment are below 20 % (18 %), while the situations when is observed distress on some life forms are around 2 % (based on 474 collecting days, during the studied period).